2021
DOI: 10.3389/fphar.2021.625546
|View full text |Cite
|
Sign up to set email alerts
|

Three Selected Edible Crops of the Genus Momordica as Potential Sources of Phytochemicals: Biochemical, Nutritional, and Medicinal Values

Abstract: Momordica species (Family Cucurbitaceae) are cultivated throughout the world for their edible fruits, leaves, shoots and seeds. Among the species of the genus Momordica, there are three selected species that are used as vegetable, and for medicinal purposes, Momordica charantia L (Bitter melon), Momordica foetida Schumach (Bitter cucumber) and Momordica balsamina L (African pumpkin). The fruits and leaves of these Momordica species are rich in primary and secondary metabolites such as proteins, fibers, mineral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 119 publications
0
17
0
Order By: Relevance
“…M. charantia fruits are rich in proteins and proteins account for 18.02% of their dried weight. 3,4 Our previous studies have identified a novel insulin receptor-binding protein mcIRBP from M. charantia . 5,6 mcIRBP is a 68-amino-acid-residue polypeptide that would be cleaved into small fragments after ingestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M. charantia fruits are rich in proteins and proteins account for 18.02% of their dried weight. 3,4 Our previous studies have identified a novel insulin receptor-binding protein mcIRBP from M. charantia . 5,6 mcIRBP is a 68-amino-acid-residue polypeptide that would be cleaved into small fragments after ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in many traditional and folk medicines for a wide range of medical applications, such as diabetes, obesity, and inflammation. 1–4 Several nutritional and nutraceutical components with anti-hyperglycemic activities have been identified from M. charantia . For example, the M. charantia insulin receptor-binding protein (mcIRBP) interacts with an insulin receptor and modulates glucose homeostasis in diabetic mice.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, this species has been regarded as a gifted plant by some rural populations. Some reviews have been published about Cucurbitaceae and Momordica species, particularly focusing on Momordica charantia , the most studied species of the genus (Dhiman et al 2012 ; Bharathi and John 2013 ; Shah et al 2014 ; Omokhua-Uyi and Van Staden 2020 ; Muronga et al 2021 ). Different aspects of M. balsamina have also been reported in these reviews, mostly covering its nutritional and medicinal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Momordica species have been reported to contain a wide variety of compounds, including triterpenoids, saponins, oils, steroids, glycosides, and flavonoids. These compounds were mostly described in M. charantia, M. balsamina and M. foetida [4,14,48,49] but chemical insights on M. cardiospermoides are still lacking. The computational tools used herein, assisted in the unravelling of the metabolome of this species, reported here for the first time.…”
Section: Detailed Exploration Of the Chemical Space Of Momordica Speciesmentioning
confidence: 99%
“…The Momordica genus comprises 59 species, geographically distributed across the globe (47 in Africa, 12 in Australia and Asia) [2,3]. Momordica species are cultivated not only for their nutritional purposes but also for traditional use in the treatment of various ailments [4]. These include diabetes-related conditions [5], cancer [6] and inflammatory diseases [7].…”
Section: Introductionmentioning
confidence: 99%